(untitled) (World Bulletin of Public Health, 2024)
This article identifies priorities for the development of the educational process based on the application of modern technologies in the higher education system of our Republic, analysis of their capabilities. Studies of the existing practice are also considered when drawing up scientifically based conclusions on the introduction of modern technologies in higher education